Optimalisasi Pelayanan Keperawatan Jiwa Di Panti Rehabilitasi Nyaman Jiwo Basung Pancuranmas Secang Magelang - Muhammad Khoirul Amin; Noviyana Pujihastusi; Apridira Diar Nugrahani; Esti Ria Aigustina; Mardiyana Agustina (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2022)
Abstract: Based on a preliminary survey with the owner of the rehab, it was found that the Nyaman Jiwo Rehab has a total of 35 patients being treated, 6 nurses who take care of patients with mental disorders every day. The owner of the rehab stated that the foundation already has a concept plan for developing vocational therapy skills including making agricultural land (vegetables, secondary crop), animal husbandry (cows, goats, ducks), sewing skills and cooking/cooking skills. It is hoped that through the rehabilitation services at the Nyaman Jiwo Rehab, the patient will be able to be independent "Migunani Tumraping Liyan" meaning that it is useful for others. The purpose of the Integrated Community Service (PPMT) is to increase the knowledge of nursing home nurses so that they can be used as a provision in encouraging the realization of one of the missions of the Nya-man Jiwo Rehabilitation Institution, which is to provide physical, psychosocial, spiritual therapy and skills/productive economic efforts. This service method uses 4 stages, namely preparation, socialization, training and also assistance in the application of MPKP, assistance in patient independence activities, and also assistance in morning exercise activities. This activity received a good response from the owner of the orphanage and also the nurses. Participants were very enthusiastic about the activities given to them.             Keywords: psychiatric nursing; rehab; services Abstrak: Berdasarkan survei pendahuluan dengan pemilik panti, di dapatkan bahwa Panti Rehabilitasi Nyaman Jiwo ini memiliki sejumlah 35 pasien yang dirawat, 6 perawat yang setiap harinya merawat pasien-pasien dengan gangguan jiwa. Pemilik Panti mengemukakan bahwa, yayasan sudah memiliki rencana konsep pengembangan vokasional terapi ketrampilan meliputi pembuatan lahan pertanian (sayur mayor, polo wijo), peternakan (sapi, kambing, bebek), ketrampilan menjahit dan tata boga/memasak. Diharapkan melalui layanan rehabilitasi di Yayasan Panti Rehabilitasi Nyaman Jiwo, pasien mampu mandiri “Migunani Tumraping Liyan “artinya bermanfaat bagi yang lain. Tujuan Pengabdian pada Masyarakat Terpadu (PPMT) adalah untuk meningkatkan pengetahuan perawat Panti sehingga bisa digunakan sebagai bekal dalam mendorong terwujudnya salah satu misi Panti Rehabilitasi Nyaman Jiwo yaitu memberikan terapi fisik, psikososial, spiritual dan ketrampilan/ usaha ekonomi produktif. Metode pengabdian ini menggunakan 4 tahapan yaitu persiapan, sosialisasi, pelatihan dan juga pendampingan dalam penerapan MPKP, pendampingan dalam kegiatan kemandirian pasien, dan juga pendampingan dalam kegiatan senam pagi. Kegiatan ini mendapatkan sambutan yang baik dari pemilik panti dan juga perawat yang ada. Peserta sangat antusias dengan kegiatan yang diberikan kepada mereka. Kata kunci: keperawatan jiwa; panti rehabilitasi; pelayanan